Simulation of boreal black spruce chronosequences: Comparison to field measurements and model evaluation - Gower, Stith T.; Bond-Lamberty, Ben; McMillan, Andrew; Goulden, Michael L. (Journal of Geophysical Research, 2006)
This study used the Biome Biogeochemical Cycles (Biome-BGC) process model to simulate boreal forest dynamics, compared the results with a variety of measured carbon content and flux data from two boreal chronosequences in northern Manitoba, Canada, and examined how model output was affected by water and nitrogen limitations on simulated plant production and decomposition. Vascular and nonvascular plant growth were modeled over 151 years in well-drained and poorly drained forests, using as many site-specific model parameters as possible. Measured data included (1) leaf area and carbon content from site-specific allometry data, (2) aboveground and belowground net primary production from allometry and root cores, and (3) flux data, including biometry-based net ecosystem production and tower-based net ecosystem exchange. The simulation used three vegetation types or functional groups (evergreen needleaf trees, deciduous broadleaf trees, and bryophytes). Model output matched some of the observed data well, with net primary production, biomass, and net ecosystem production (NEP) values usually (50 ? 80% of data) within the errors of observed values. Leaf area was generally underpredicted. In the simulation, nitrogen limitation increased with stand age, while soil anoxia limited vascular plant growth in the poorly drained simulation. NEP was most sensitive to climate variability in the poorly drained stands. Simulation results are discussed with respect to conceptual issues in, and parameterization of, the Biome-BGC model.